The Christian Church in China Should Establish a Church with a Formal Church Structure - ZHANG, Hua (Journal of Research for Christianity in China (JRCC), 2025)
This paper proposes that China should establish a church with a formal church structure. It elaborates on several aspects: what constitutes a church structure, why it should be established, how to establish it, and the significance of establishing a church with a formal structure. The author argues that although Chinese Christianity has not yet established a church with a formal structure, it has in fact been exploring this for many years. Chinese Christianity should seize the opportunity to establish the “Chinese Christian Church” as soon as possible.